(untitled) (Bangladesh Journal of Botany, 2026)
Cytogenetic analysis was carried out in Oxalis corymbosa, O. corniculata, O. latifolia and O. triangularis for precise characterization. Several small orcein-stained heterochromatic regions were found in the interphase nuclei of O. corymbosa and O. triangularis while large heteropycnotic blocks were observed in O. corniculata and O. latifolia. Darkly stained heterochromatic regions were scattered in the prophase chromosomes of O. corymbosa. In contrast, O. corniculata and O. triangularis possessed prophase chromosomes with homogenously staining along the entire length while O. latifolia stained gradually from one end to another. In four species, the nature of staining indicates the probable presence of facultative heterochromatin. The four Oxalis species showed discrete and species-specific CMA- and DAPI banding patterns based on the distribution of GC- and AT-repetitive sequences. Bangladesh J. Bot. 55(2): 427-431, 2026 (June)